Penerapan Rehabilitasi Terhadap Korban Penyalahguna Narkotika Ditinjau dari Teori Kemanfaatan: Studi Putusan di Pengadilan Negeri Padang - Harisa, Yossi; Ismansyah, Ismansyah; Mulyati, Nani (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study examines the application of integrated assessments in sentencing drug abuse offenders to rehabilitation, using the theory of utility. Employing normative and sociological legal methods, data were collected from court decisions and interviews. Findings indicate that judges consider integrated assessments when the offender is not involved in drug trafficking. While rehabilitation offers legal and health benefits, its implementation is hindered by vague regulations, limited funding, and inadequate facilities.